Ecological Sanitation : Social Factors Impacting Use of EcoSan in Rural Indonesia - Albrecht, Martin; Blackett, Isabel; Arianto, Ikabul (World Bank, Washington, DC, 2012)
Access to improved sanitation remains a huge challenge in Indonesia. Joint Monitoring Program (JMP) 2010 data indicate that around 38 percent of the rural population has access to improved sanitation services and that open defecation remains a widespread practice for over 60 million Indonesians. The persistence of old habits and a lack of awareness form the basis of many challenges in the Indonesian sanitation sector. To change this situation there is a need to focus on changing sanitation and hygiene behavior within communities, in addition to increasing investment in sanitation services. The majority of Indonesians are Muslims (88 percent), and Islamic teachings provide instruction and guidance on sanitation habits and behaviors. The teaching requires that running water, if available, should be used for anal cleansing and certain materials, including human excreta and urine, are regarded as najis (ritually unclean). Apart from the 'natural' feelings of disgust that most people express towards human excreta which result in anal cleansing, Islam requires ritual cleansing after being in contact with materials that are considered to be najis. However, the use of water for anal cleansing also appears to be a cultural habit as non-Muslim Indonesians also use water for anal cleansing, a fact confirmed by the study results.